The body snatchers affair : a Carpenter and Quincannon mystery - Muller, Marcia (Muller, Marcia. Carpenter and Quincannon mystery, 2015)
Conducting a dual investigation in the opium dens of San Francisco's Chinatown, Sabina Carpenter and John Quincannon search for missing millionaires against a backdrop of a brewing Tong war.